Electron and vibrational spectroscopies using DFT, plane waves and pseudopotentials: CASTEP implementation - Milman, V; Refson, K; Clark, S; Pickard, C; Yates, JR; Gao, S; Hasnip, P; Probert, M; Perlov, A; Segall, MD (2010)
Density functional theory can be used to interpret and predict spectroscopic properties of solid-state materials. The relevant computational solutions are usually available in disparate DFT codes, so that it is difficult to use a consistent approach for analyzing various spectroscopic features of a given material. We review the latest developments that are aimed to provide a collection of analytical tools within one DFT package, CASTEP. The applications covered include core-level EELS, solid-state NMR, optical properties, IR and Raman spectroscopy. We present also results of the EELS analysis of NbO and Nb 2O 5 that show the first published example of CASTEP spectra from d-states. Raman activities calculated for a test set of small molecules and the convergence requirements for such calculations are discussed. © 2010 Elsevier B.V.